2006
DOI: 10.1359/jbmr.060721
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel TRPV6 Expression in Human Duodenum: Different Relationships to the Vitamin D System and Aging in Men and Women

Abstract: Intestinal absorption of calcium affects bone mineralization and varies greatly. In human duodenum, expression of the calcium channel TRPV6 was directly related to blood 1,25-dihydroxyvitamin D in men, but effects of age with lower median vitamin D receptor levels were more significant in women.Introduction: The TRPV6 calcium channel/transporter is implicated in animal studies of intestinal calcium absorption, but in humans, its role and relationship to differences in mineral metabolism is unclear. We aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…This channel facilitates calcium entry into the enterocytes. TRPV6 is highly regulated by 1,25(OH) 2 D and is most highly expressed in the duodenum compared to the jejunum and ileum [4]. In women, TRPV6 levels decline with aging, which partially explains the age-associated decline in calcium absorption [5].…”
Section: Intestinal Calcium Absorptionmentioning
confidence: 99%
“…This channel facilitates calcium entry into the enterocytes. TRPV6 is highly regulated by 1,25(OH) 2 D and is most highly expressed in the duodenum compared to the jejunum and ileum [4]. In women, TRPV6 levels decline with aging, which partially explains the age-associated decline in calcium absorption [5].…”
Section: Intestinal Calcium Absorptionmentioning
confidence: 99%
“…Changes in the expression of VDR leading to vitamin D resistance with aging have also been elaborated in recent literature. Several studies have reported association of aging with decrease in the expression of VDR in bone, intestine, and muscle tissues [38][39][40]. Various factors that decrease with aging have been identified to influence VDR such as estrogen, growth hormones, and vitamin D itself [11,41].…”
Section: Vitamin D and Agingmentioning
confidence: 99%
“…Walters et al [22] characterized TRPV6 transcript expression in normal human intestinal biopsies. TRPV6 transcripts were detected in the duodenum but not in the ileum.…”
Section: Transcellular Pathwaymentioning
confidence: 99%
“…This decrease occurs, at least in part, because of a declination in the serum calcitriol levels, but in addition, a resistance to the actions of calcitriol in the intestine has been reported [22]. Although the mechanisms are poorly known, in women the lack of estrogen during menopause could partially explain this age-associated intestinal resistance to calcitriol.…”
Section: Intestinal Ca2+ Absorption Under Different Physiological Conmentioning
confidence: 99%
See 1 more Smart Citation